IMPAIRED MSC-MEDIATED NEUROGLIAL PROTECTION IN PROGRESSIVE MS. Issue 12 (15th November 2016) - Sarkar, Pamela; Redondo, Juliana; Kemp, Kevin; Wilkins, Alastair; Scolding, Neil; Rice, Claire
Abstract : Multipotent mesenchymal stromal cells (MSCs) have neuro- and glial protective properties and can influence the differentiation and maturation of oligodendrocytes. Clinical trials employing autologous MSC transplantation for the treatment of multiple sclerosis (MS) and other neurodegenerative diseases are ongoing. Extending previous studies, we have performed detailed analysis of the phenotype of MSCs derived from patients with MS using marrow samples donated as part of the 'ACTiMuS' trial which is examining the efficacy of unfractionated autologous bone marrow in progressive MS (NCT01815632 ). In keeping with previous findings, MS MSCs have comparable mesenchymal differentiation potential to MSCs isolated from control subjects. However, donor age negatively correlates with clonogenic potential and premature senescence. Using in vitro models of neuroglial toxicity, we have demonstrated that the neuroglial protective effects of soluble factors produced by MSCs decline with expansion in vitro. Significantly, media conditioned by MSCs isolated from patients with long duration of progressive disease have reduced neuroglial protective capacity. Using tandem mass spectroscopy, we have identified over 40 factors whose secretion by MSCs is altered in progressive MS. Further work will explore their relevance to MS pathogenesis and repair with the aim of identifying new drug candidates and optimisation of cell-based therapy for MS.